Cross-sectional association between red blood cell distribution width and regional cerebral tissue oxygen saturation in preterm infants in the first 14 days after birth - Mu, Yuju; Wang, Hua; Tian, Mengting; Hu, Yong; Feng, Yi; Lu, Ruifeng; He, Qi; Jiang, Shouliang; Huang, Jinglan; Duan, Surong; Mu, Dezhi (Frontiers in Pediatrics, 2023)
Background: Hypoxia can threaten the metabolic functions of different systems in immature neonates, particularly the central nervous system. The red blood cell distribution width (RDW) has recently been reported as a prognostic factor in neurologic diseases. Herein, we examined the correlation between RDW and regional cerebral tissue oxygen saturation (rcSO2).This cross-sectional study included 110 preterm infants born at a gestational age (GA) of <32 weeks, or with a birth weight (BW) of <1500 g at our institution between January and June 2022.The rcSO2 was monitored using near-infrared spectroscopy, and RDW was extracted from the complete blood count during the first 14 days after birth. RDW and rcSO2 measurements were analyzed using a cross-sectional research method.Results: We divided the study population into two groups, with a mean rcSO2 value over the first 14 days. Fifty-three preterm had rcSO2 ≥ 55% and 57 <55%. The 14-days-mean in the study population showing an association of lower rcSO2 values with higher RDW values. Significantly higher RDW values were observed in the low rcSO2 group compared with those in the high rcSO2 group.Threshold effect analysis showed that rcSO2 decreased with RDW values ≥18% (β, -0.03; 95% CI, -0.04–0.02; p<0.0001). After adjusting for potential confounders, an RDW of ≥18% was determined as the predictive cutoff value for preterm infants with low rcSO2 (Model I: